2008
DOI: 10.1523/jneurosci.2870-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Distortions of Reward Probability without Choice

Abstract: Reward probability crucially determines the value of outcomes. A basic phenomenon, defying explanation by traditional decision theories, is that people often overweigh small and underweigh large probabilities in choices under uncertainty. However, the neuronal basis of such reward probability distortions and their position in the decision process are largely unknown. We assessed individual probability distortions with behavioral pleasantness ratings and brain imaging in the absence of choice. Dorsolateral fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 68 publications
5
69
1
1
Order By: Relevance
“…This suggests that the striatum is preferentially involved in coding parametric reward value rather than reward uncertainty. Such a conclusion is consistent with human imaging findings (Tobler et al 2008) indicating that striatal activation is dependent on reward probability but not on reward uncertainty in a very similar probabilistic Pavlovian conditioning task. Furthermore, we found that only a small number of neurons showed negative correlations between CS-related activity and reward probability even though positive correlations between CS-related activity and reward probability were substantial and numerous.…”
Section: Cs Tonic Cs Phasicsupporting
confidence: 90%
“…This suggests that the striatum is preferentially involved in coding parametric reward value rather than reward uncertainty. Such a conclusion is consistent with human imaging findings (Tobler et al 2008) indicating that striatal activation is dependent on reward probability but not on reward uncertainty in a very similar probabilistic Pavlovian conditioning task. Furthermore, we found that only a small number of neurons showed negative correlations between CS-related activity and reward probability even though positive correlations between CS-related activity and reward probability were substantial and numerous.…”
Section: Cs Tonic Cs Phasicsupporting
confidence: 90%
“…For instance, some studies find that VS activation peaks at intermediate probability levels, consistent with maximal uncertainty (Cooper and Knutson, 2008;Dreher et al, 2006;Knutson et al, 2005;Preuschoff et al, 2006). Other studies, however, have reported linear effects of anticipated reward probability on VS activation (Abler et al, 2006;Hsu et al, 2009;Tobler et al, 2008;Yacubian et al, 2006). A large subsequent study investigated the possibility that different subcomponents within the VS showed greater sensitivity to anticipated reward magnitude vs probability (Yacubian et al, 2007).…”
Section: Reward Processing In the Human Vsmentioning
confidence: 99%
“…The loci of activations and the nature of nonlinear probability functions can be contrasted with those from two recent experiments (Berns et al, 2008;Tobler et al, 2008). Numerous factors may explain discrepancies between these studies: the way probabilities were presented to subjects (alphanumerically or learned through experience), the experience of feedback, the range of probabilities used, the context (positive or negative outcomes), and the specific analyses conducted.…”
mentioning
confidence: 99%